Spatial segmentation of Jiali Fault’s Holocene activity in the southeastern Tibetan Plateau - Shijie Liu; Hengxing Lan; Alexander Strom; Langping Li; Han Bao (npj Natural Hazards)
Abstract Jiali Fault plays a key role in the dextral fault system in the southeastern Tibetan Plateau. Although it forms a striking topographic lineament the Yigong and Parlung Rivers, evidence for faulting in the Holocene has been equivocal. In this study, Holocene sediment deformation caused by the Jiali Fault was discovered in the debris flow fan near the Guxiang barrier lake. A palaeo-earthquake event that occurred between 3494 and 2865 cal B.P. was revealed, as evidenced by geological, seismic, and radiocarbon dating investigations. On the basis of a compilation of dating results, the middle segment of the Jiali Fault was proposed to belong to a Holocene active fault. This was attributed to the strong influence of the continued north eastwards compression of the Indian Plate and the clockwise rotation of the eastern Himalayan syntaxis. These findings provide new insights into the tectonic implications and earthquake activity of the southeastern Tibetan Plateau.